Dinoflagellate composition and environmental conditions in the Xuan Dai Bay, South-Central Vietnam - Huynh, Thi Ngoc Duyen; Tran, Thi Minh Hue; Tran , Thi Le Van; Phan, Tan Luom; Nguyen, Tam Vinh; Nguyen, Ngoc Lam; Doan-, Nhu Hai (Vietnam Journal of Marine Science and Technology, 2024)
The dinoflagellate community was investigated in association with environmental factors using a data set in April 2021 and April 2022 in Xuan Dai Bay, South-Central Viet Nam. Environmental variables, including physical parameters and dissolved inorganic nutrients, were measured in April 2022. Seventy-three dinoflagellate taxa were identified for Xuan Dai Bay. There was a significant difference in the number and abundance of dinoflagellates between two parts of the bay, the upper and lower bay. The study showed that dinoflagellates favored an area with good water exchange and were less affected by aquaculture activities. Principal component analysis (PCA) was used to explore the relative abundances of different phytoplankton groups, their diversity indices, and environmental variables at the surface and bottom layers of the two parts of the bay. The results showed that dinoflagellates correlated to physical parameters (e.g., PAR, salinity, temperature) at the surface layer and nutrients at the bottom layer. Dinoflagellates and diatoms are mixotrophic and strongly correlated at the bottom layer in Xuan Dai Bay. This strong relationship in the bay was because of the dominance of a heterotrophic genus, Protoperidinium. The present study provided characteristics of the dinoflagellates in Xuan Dai Bay and the possible impacts of environmental parameters on their abundance. The results can be used for further studies and possibly managing of dinoflagellate blooms in coastal waters.